Analisis Strategi Pemasaran Bank Syariah Dalam Meningkatkan Daya Saing - Darma, Surya; Ramadani, Alpin (TARBIYAH: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This study aims to analyze the marketing strategies implemented by Islamic banks in increasing competitiveness in the increasingly competitive banking market. The method used in this study is a qualitative method with a literature study approach, which includes analysis of various literature, articles, and previous studies related to Islamic bank marketing. The results of this study indicate that the marketing strategies implemented by Islamic banks play an important role in increasing their competitiveness, by emphasizing market understanding, customer segments, and the application of sharia principles that avoid usury practices, thus attracting customers who prioritize Islamic values.